PKM Providing Complementary Foods For Breast Milk (CFB) Based on Local Wisdom In The Community Of Lamjamee Village, Jayabaru District, Banda Aceh City: PKM Pemberian Makanan Pendamping Asi (MP-ASI) Berbasis Kearifan Lokal Pada Masyarakat Desa Lamjamee Kecamatan Jayabaru Kota Banda Aceh - Rosdiana, Eva; Nuzul ZA, Raudhatun; Apriani Hasanah Hrp, Laila; Lestari, Soraya (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Nutrition issues and substandard complementary feeding practices remain a challenge in Aceh Province, particularly in Lamjamee Village, Jayabaru District. Many mothers of toddlers are accustomed to providing instant foods and packaged snacks that lack nutrition. This community service activity aims to improve the knowledge and skills of housewives and integrated health post (Posyandu) cadres in utilizing local food ingredients, namely peugaga leaves (Centella asiatica), as nutritious complementary feeding. Implementation methods included counseling, training, and participatory cooking demonstrations using PowerPoint presentations, educational videos, and pre- and post-test questionnaires for evaluation. The activity results showed a 100% increase in participants' knowledge and skills related to the processing and utilization of local food ingredients. Participants also began developing innovative complementary feeding recipes and micro-business opportunities based on peugaga leaves. This program has proven effective in increasing nutritional awareness and empowering communities through local wisdom. In conclusion, education and training on complementary feeding (MP-ASI) based on local ingredients can be a sustainable solution for improving child nutrition while supporting family food security in Lamjamee Village.